Right-sizing solar irrigation pumps: in India, and beyond - Verma, Shilp (CGIAR System Organization, 2023)
Solar irrigation pumps can bring significant benefits for food security, livelihoods, and the environment. They run on clean, renewable energy, with no reliance on costly and polluting fossil fuels, and once installed, they have no running costs – providing 1,400–2,200 hours of free, dependable energy per year, contributing to food security and boosting farmers’ incomes for decades. Farmers are understandably enthusiastic about the adoption of these pumps. However, the lack of running costs means there is no incentive to limit pumping, which can lead to the depletion of groundwater resources.